Experimental Study of Vibration Sensitivity in Unidirectional Polarimetric Current Sensors - Tantaswadi, P.; Maheshwari, S.; Tangtrongbenchasil, C. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Accuracy of current measurement in optical fiber current sensor is affected by the environment perturbations to the sensing fiber such as mechanical vibrations, acoustic perturbations, and temperature changes. This paper presents the experimental study of the effect of mechanical vibrations on the current measurement error. Results show that current measurement error varies linearly with the amplitude of vibration. We also develop a novel mathematical model for vibration sensitivity in unidirectional polarimetric current sensors. In this paper, we believe that it is the first time that the effect of vibration to the single-mode-sensing fiber on the current measurement error in fiber optic polarimetric current sensor is formulated. Similation results agree well with the experimental results. Keywords: current sensor, polarimetry Corresponding author: E-mail: cast@kmitl.ac.th